(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article delves into the correspondence of Bukhari letters dispatched to various destinations by Amir Haydar, a prominent figure of the Mangit dynasty. The examination of these letters sheds light on the intricate social and political dynamics that characterized the 19th-century Bukhara Emirate, offering insights into both the conditions of the populace within the Emirate’s domain and the governance practices of the period. Through a careful analysis of these historical documents, readers gain invaluable knowledge about the multifaceted facets encompassing the social, economic, and educational spheres of the Mangit dynasty in Bukhara.